INTERMARKET INFLUENCE BETWEEN TRADITIONAL STOCK MARKETS AND CRYPTOCURRENCIES: A CASE STUDY OF JSX AND BTC - Chandra, Reddy (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
This study explores the intermarket dynamics between the Jakarta Stock Exchange Composite Index (JSX) and Bitcoin (BTC), focusing on their behavior during periods of market stress, such as the COVID-19 pandemic. Using historical data from 2017 to 2024, the research employs volatility analysis, Vector Autoregression (VAR) models, and correlation analysis to investigate the volatility spillovers and interdependencies between these two distinct markets. The findings reveal that BTC exhibits significantly higher volatility compared to JSX and USD/IDR, underscoring its high-risk nature. The study also uncovers that while volatility spillovers from JSX to BTC are present, the reverse is less pronounced, suggesting that traditional stock markets can influence cryptocurrency markets during periods of economic stress. The results have important implications for investors, highlighting the need for careful risk management and portfolio diversification strategies, especially in emerging markets like Indonesia.